The effect of the type of preparation on the deposit of copper while spraying the winter oilseed rape - Dereń, Katarzyna; Szewczyk, Antoni; Sekutowski, Tomasz Robert; Kowalska-Góralska, Monika (Agricultural and Food Science, 2018)
The aim of the research was to determine the copper deposit volume on winter oilseed rape in three development phase (according to the BBCH scale: 12, 14 and 16). The experiment was performed in triplicate at the spraying speed of 0.86 m s-1. Two working fluids were used: foliar fertilizer Mikrovit Copper 80 and a nanocopper preparation, at the dose of 160 g Cu ha-1. The deposition treatment of the plants was conducted in the spraying chamber ‘Aporo1’ at two pressures (0.20 and 0.28 MPa), using two different types of flat fan nozzles. The dried rape plants were mineralized, and then, in order to determine the deposit, the Cu element concentration was measured using the spectrometer. The largest deposit of copper was obtained using the foliar fertilizer Mikrovit Copper 80 and using a double flat fan nozzle DF 120-02. The statistical analysis of the results of the study showed a significant effect of the type of liquid used on the value of copper deposit on winter oilseed rape plants.